(untitled) (Research, Society and Development, 2025)
Smoking is one of the most prevalent addictions worldwide. It alters the patient’s immune response against periodontopathogenic microorganisms, compromising the defense system and potentially triggering periodontal collapse, periodontitis. Periodontitis and smoking have a major impact on the immune system, posing a huge challenge to the patient’s health and well-being. Therefore, it is extremely important for dentists to understand the impacts of smoking on patients with periodontitis, so that they can establish a better diagnosis and prognosis, in addition to raising patient awareness and encouraging them to quit smoking. The objective of this review was to validate the immunoinflammatory relationship between smoking and periodontitis in order to provide scientific knowledge that supports decision-making in order to promote health. An integrative literature review was carried out, selecting 8 articles, according to the exclusion criteria, to answer the guiding question "What is the immunoinflammatory influence of smoking on periodontitis and the consequences for periodontal health?" CONCLUSION: Smoking appears to exacerbate the local inflammatory response by increasing pro-inflammatory cytokines such as IL-1β, deregulating the balance of bone remodeling mediators such as RANKL/OPG, and altering the composition of the oral microbiota, favoring pathogenic species. In addition, smoking modulates the adaptive immune response, affecting the levels of antibodies against periodontal and commensal pathogens, and may interfere with the production of antimicrobial peptides important in host defense, increasing the prevalence, severity, and progression of periodontitis.